"The emerging role of capivasertib in breast cancer". (June 2022) - Andrikopoulou, Angeliki; Chatzinikolaou, Spyridoula; Panourgias, Evangelia; Kaparelou, Maria; Liontos, Michalis; Dimopoulos, Meletios-Athanasios; Zagouri, Flora
Abstract: Over 50% of breast tumors harbor alterations in one or more genes of the phosphatidylinositol 3-kinase (PI3K) pathway including PIK3CA mutations (31%), PTEN loss (34%), PTEN mutations (5%) and AKT1 mutations (3%). While PI3K and mTOR inhibitors are already approved in advanced breast cancer, AKT inhibitors have been recently developed as a new therapeutic approach. Capivasertib (AZD5363) is a novel, selective ATP-competitive pan-AKT kinase inhibitor that exerts similar activity against the three AKT isoforms, AKT1, AKT2, and AKT3. Preclinical studies demonstrated efficacy of capivasertib in breast cancer cell lines as a single agent or in combination with anti-HER2 agents and endocrine treatment, especially in tumors with PIK3CA or MTOR alterations. Phase I/II studies demonstrated greater efficacy when capivasertib was co-administered with paclitaxel, fulvestrant in hormone receptor (HR)-positive, HER2-negative breast cancer or olaparib. The recommended phase II dose of capivasertib as monotherapy was 480 mg bid on a 4-days-on, 3-days-off dosing schedule. Toxicity profile proved to be manageable with hyperglycemia (20–24%), diarrhea (14–17%) and maculopapular rash (11–16%) being the most common grade ≥3 adverse events. Ongoing Phase III trials of capivasertib in combination with fulvestrant (CAPItello-291), CDK4/6 inhibitor palbociclib (CAPItello-292) and paclitaxel (CAPItello- 290) will better clarify the therapeutic role of capivasertib in breast cancer. Highlights: Phosphatidylinositol-3-kinase (PI3K)/Akt (PI3K/AKT) pathway is one of the most commonly altered pathways in breast cancer. Capivasertib (AZD5363) is a highly potent Akt kinase inhibitor with activity against the three isoforms AKT1, AKT2, and AKT3. Preclinical studies demonstrated efficacy of capivasertib either alone or in combination with anti-HER2 agents, chemotherapy and endocrine treatment. Dose-limiting toxicities include hyperglycemia (20–24%), diarrhea (14–17%) and maculopapular rash (11–16%). Capivasertib increased susceptibility to paclitaxel (PAKT, BEECH), fulvestrant (NCT01226316, FAKTION) or Olaparib (ComPAKT).